Development in Africa refocusing the lens after the Millennium Development Goals - Kararach, George; Besada, Hany ca. 20./21. Jh; Shaw, Timothy M. 1945- (Policy Press, 2015)
This important book looks beyond the Millennium Development Goals to highlight twelve major public policy conversations about the continent post-2015, arguing that Africa as a continent must work on developing a society that is socially, economically and politically inclusive